Strategic communication, media synergies, and trust in rural development: A case study from Albania - Boshnjaku, Anila; Gjeloshi, Aljula; Çoku, Belioza (Edelweiss Applied Science and Technology, 2025)
This study explores how strategic communication can enhance rural development in Albania by examining the interplay between media ecosystems, trust, and innovation. In response to growing distrust in traditional media and fragmented digital engagement, the research investigates how hybrid communication strategies—blending traditional, digital, and interpersonal channels—can better resonate with rural communities. Through semi-structured interviews with communication professionals, local leaders, and development practitioners across Albania, the study applies thematic analysis to uncover stakeholder perceptions and practices. Findings reveal a deep disconnect between institutional messaging and rural realities, largely due to trust deficits and the limited use of interactive, inclusive communication formats. Yet, credible innovations are emerging, such as combining face-to-face outreach with social media or community radio. Trusted local intermediaries—like community leaders and radio hosts—play a pivotal role in bridging this gap. The study introduces a “relational synergy” framework emphasizing the alignment of message, messenger, and media ecology. It concludes that building trust, ensuring cultural relevance, and co-creating content are essential for effective communication in rural areas. Recommendations include investing in digital literacy, leveraging local “trust filters,” and designing participatory, hybrid communication strategies to support inclusive rural transformation.